Enhancing effect of nitrogen on grain production of hybrid maize in Chitwan valley (Agronomy Journal of Nepal, 2013)
Nitrogen is one of the key factors for increased grain production of hybrid maize. A newly developed hybrid maize variety Rampur Hybrid-2 was evaluated for grain production by the application of different levels of nitrogen (60, 120 and 180 kg N/ha) at varying plant densities (55555, 66666 and 83383 plants/ha) along with 60 kg P2O5 and 40 kg K2O /ha in the acidic soil (pH 5.3) of National Maize Research Program, Rampur, Chitwan during the years of 2008/09 and 2009/10. Factorial randomized complete block design (RCBD) with three replications was the design of experiment. The crop was planted at the plot size of 18 m2 (3.6 m × 5 m). maize was planted in the month of September and harvested in February. The result indicated a sharp response of nitrogen application to this crop whereas the effect of density was observed to be non-significant. Two years mean yield results showed that highest grain yield (11.10 t /ha) was recorded when the crop was supplied with 180 kg nitrogen and with 83383 plants /ha followed by the crop supplied with 120 kg N /ha and 66,666 plant population (10.69 t /ha). The experimental results revealed that application of high dose of N (180 kg N /ha) could help increase hybrid maize grain production in the acidic soils of Chitwan valley. Agronomy Journal of Nepal (Agron JN) Vol. 3. 2013, Page 33-41 DOI: http://dx.doi.org/10.3126/ajn.v3i0.8984